Reformas al codigo laboral a fin de implementar la reinserción laboral de los trabajadores que han cumplido una pena privativa de la libertad no mayor de treinta días. - Pineda Llivisaca, Oswaldo Enrique (2016)
The time in which we live is had of constant changes and social transformations in those that we participate direct or indirectly and, in all these social processes the necessities are always present, it is hence that every year the number of unemployed is not increased because of exclusive hardships of the freedom bigger than thirty days, such difficulties impede the individual's labor and economic development that doesn't allow him/her to be unwrapped professionally in the society. Reason enough to have selected the topic titled investigative "REFORMATIONS TO THE LABOR CÒDIGO TO END OF IMPLEMENTING LABOR REINSERCIÓN OF THE WORKERS THAT have COMPLETED An EXCLUSIVE PAIN OF THE FREEDOM NOT bigger DE THIRTY DAYS", which intended as objective to determine reformations to the Labor Code in order to implement the labor reinserción of the workers that have completed an exclusive pain of the freedom not bigger than thirty days, that which generates bigger unemployment rate in the country, for that which was required of the use of some methods among which are counted the inductive, deductive, historical compared and hypothetical deductive, the same ones that aided by the bibliographical techniques, he/she interviews and it interviews, they allowed the attainment of the outlined goals. As in all investigative process, a hypothesis was formulated, which makes reference to that the Labor code of Ecuador attempts against the artificial security of the Ecuadorian workers that you/they have completed an exclusive pain from the freedom when not reinserting them laborly. Once fulfilled the signal stages and having obtained the respective field information, you proceeded to process it to the same one, being known that private people of the freedom manifested that programs of labor reinserción don't exist for people with privation of the freedom and that at the present time he/she is not carried out this procedure, because when being been absent during thirty days or less he/she automatically gets lost the work. On the other hand the lawyers in free exercise of the right are also of agreement with this civic opinion. With the gathered information he/she is carried out the reformation proposal, important point of the elaborated project, to conclude with the respetivas conclusions and recommendations.